Signatures of diversifying selection at EST‐SSR loci and association with climate in natural Eucalyptus populations. Issue 20 (10th October 2013) - Bradbury, Donna; Smithson, Ann; Krauss, Siegfried L.
Abstract Understanding the environmental parameters that drive adaptation among populations is important in predicting how species may respond to global climatic changes and how gene pools might be managed to conserve adaptive genetic diversity. Here, we used Bayesian FST outlier tests and allele–climate association analyses to reveal two Eucalyptus EST‐SSR loci as strong candidates for diversifying selection in natural populations of a southwestern Australian forest tree, Eucalyptus gomphocephala (Myrtaceae). The Eucalyptus homolog of a CONSTANS‐like gene was an FST outlier, and allelic variation showed significant latitudinal clinal associations with annual and winter solar radiation, potential evaporation, summer precipitation and aridity. A second FST outlier locus, homologous to quinone oxidoreductase, was significantly associated with measures of temperature range, high summer temperature and summer solar radiation, with important implications for predicting the effect of temperature on natural populations in the context of climate change. We complemented these data with investigations into neutral population genetic structure and diversity throughout the species range. This study provides an investigation into selection signatures at gene‐homologous EST‐SSRs in natural Eucalyptus populations, and contributes to our understanding of the relationship between climate and adaptive genetic variation, informing the conservation of both putatively neutral and adaptive components of genetic diversity.